Integration of a (–Cu–S–) n plane in a metal–organic framework affords high electrical conductivity - Abhishek Pathak (Nature Portfolio, 2019)
Metal–organic frameworks that contain metal–sulfur chains have been demonstrated to exhibit good electrical conductivity. Here, the authors integrate a 2D metal–sulfur plane into a metal–organic framework, reporting a single crystal with a high conductivity of 10.96 S/cm.